Penerapan Metode Bercerita Dengan Menggunakan Boneka Tangan untuk Meningkatkan Kognitif Pada Anak di TK Hosiana Tumatangtang - Meiske Ester Tumbel (Peneliti.net, 2022)
One aspect of development in early childhood education is the cognitive aspect. The characteristics of cognitive development in children aged 2-6 years are that children will comment on stories that are read to them, children start reading simple books, children can retell what the teacher has told them even though it is not optimal and children want to know a lot about what that he saw. Also the curiosity of children to listen to fairy tales, and to see how to play hand puppets, as well as children begin to know abstract images on hand puppets. The purpose of this study was to describe the application of the storytelling method using hand puppets to improve cognitive abilities in children at Hosiana Tumatangtang Kindergarten. While the research method used is classroom action research according to Kemmis and Mc. Taggart in Utami, et al (2013: 295) which consists of the stages of Planning, Implementation, Observation and Reflection. The target object of this research is children in the Hosiana Tumatangtang Kindergarten, totaling 12 children. In the first cycle the results achieved were 41.6%, while the results in the second cycle were 83.33%. Based on the conclusion of the research results that the use of hand puppets to improve children's cognitive abilities in children's learning activities is very important and very suitable for use in children aged 5-6 years. Based on the results of the research, it can be concluded as follows: that the application of the storytelling method through hand puppets to improve cognitive abilities in children at Hosiana Tumatangtang Kindergarten. The results of the study showed that in cycle I, only 5 children were able to achieve the learning objectives and there was an increase in cycle II which becomes 10 children who have achieved learning goals.